Russia’s Ambivalent Status-Quo/Revisionist Policies in the Arctic - Baev, Pavel (Arctic Review on Law and Politics, 2018)
Russia has been following an Arctic policy that is highly heterogeneous, combining efforts at preserving cooperation with Western neighbors with commitment to building up its own strength. Three distinct policy modes can be identified: realist/militaristic, institutional/cooperative, and diplomatic management. Each mode is based on a particular interpretation of Russia’s various interests in the High North/Arctic: nuclear/strategic, geopolitical, economic/energy-related, and symbolic. Examination of policy modes and interests shows that each combination contains some elements that focus on preserving the status quo in the Arctic, while other elements push for changes in Russia’s favor. This article finds that revisionist elements have been gaining in strength, but that current policy still attaches high value to sustaining traditional patterns, even if they demand more resources and provide fewer advantages and revenues.